A case of fatal sigmoid volvulus visualized on postmortem radiography: The importance of image optimization with multidetector computed tomography. (March 2016) - Usui, Akihito; Kawasumi, Yusuke; Hosokai, Yoshiyuki; Ishizuka, Yuya; Ikeda, Tomoya; Saito, Haruo; Funayama, Masato
Graphical abstract: Highlights: This report describes the case of a man who developed fatal sigmoid volvulus. Three dimension reformatting form CT images can illustrate the point of obstructed sigmoid colon. Image reconstruction are best performed by personnel with CT technology training. Abstract: This report describes the case of a man who developed fatal sigmoid volvulus that was identified on postmortem radiography before forensic autopsy. Postmortem radiography is useful for visualizing the body prior to autopsy. We discuss postmortem multidetector computed tomography that was tailored for optimum image quality to allow reconstruction of the fatal findings in multiple axes and in three dimensions, helping to pinpoint the anatomical sites of interest. This involves techniques such as manipulation of the scanning beam pitch and overlapping CT section acquisition. These techniques are best performed by personnel with CT technology training.